The Punan People of Batu Benau Sajau: Between Hunter-Gatherer Mobility and Contemporary Challenges - Adi Prasetijo; Yuli Prasetyo Nugroho (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This paper examines whether the Punan people of Batu Benau Sajau in North Kalimantan can be seen as a hunter-gatherer society in the contemporary context. Historically, the Punan people were known as forest nomads who relied on hunting, gathering, and seasonal mobility for their livelihoods. However, with state expansion, market penetration, and the entry of corporate concessions, this lifestyle has undergone a significant transformation. The Punan people of Batu Benau Sajau continue to maintain hunter-gatherer characteristics, including a forest-based subsistence system, seasonal mobility, and an egalitarian social structure. Their spatial cosmology also demonstrates a deep attachment to the forest landscape, which serves as the basis not only for their livelihood but also for their cultural identity. They cannot be viewed as